Strategies for Fostering Students’ Interest Using Canva Media in Mathematics Learning for Fifth-Grade Students at SD Negeri 13 Lolong - Nadiatul Rahma; Yona Syaida Oktira; Nofriza Efendi; Ayunis Ayunis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to describe strategies for fostering students’ interest in mathematics learning through canva media in grade V of SD Negeri 13 Lolong and to identify the supporting and inhibiting factors. A qualitative case study was employed with data collected through observation, interviews, and documentation, then analyzed using data reduction, display, and conclusion drawing. The subjects were the grade V teacher and five students. The results indicate that the strategies included interactive quizzes before lessons, presenting materials with visually appealing canva designs, and encouraging active student participation. Supporting factors were the availability of facilities and the attractiveness of visual media, while inhibiting factors included limited time, dependence on stable internet access, and teachers’ limited skills in using canva. Overall, canva effectively increased students’ interest in mathematics learning, although further efforts are needed to address technical and teacher-related challenges.